The impact of arm-crank position on the drag of a paralympic hand-cyclist. Issue 4 (12th March 2019) - Mannion, Paul; Toparlar, Yasin; Clifford, Eoghan; Hajdukiewicz, Magdalena; Andrianne, Thomas; Blocken, Bert
Abstract: The aerodynamic features associated with the rotation of a cyclist's legs have long been a research topic for sport scientists and engineers, with studies in recent years shedding new light on the flow structures and drag trends. While the arm-crank rotation cycle of a hand-cyclist bears some resemblance to the leg rotation of a traditional cyclist, the aerodynamics around the athlete are fundamentally different due to the proximity and position of the athlete's torso with respect to their arms, especially since both arm-cranks move in phase with each other. This research investigates the impact of arm-crank position on the drag acting on a hand-cyclist and is applied to a hill descent position where the athlete is not pedalling. Four primary arm-crank positions, namely 3, 6, 9, and 12 o'clock of a Paralympic hand-cyclist were investigated with CFD for five yaw angles, namely 0°, 5°, 10°, 15°, and 20°. The results demonstrated that the 3 and 12 o'clock positions (when observed from the left side of the hand-cyclist) yielded the highest drag area at 0° yaw, while the 9 o'clock position yielded the lowest drag area for all yaw angles. This is in contrast to the 6 o'clock position traditionally held by hand-cyclists during a descent to reduce aerodynamic drag.